New journalisms rethinking practice, theory and pedagogy - Fowler-Watt, Karen; Jukes, Stephen (Routledge research in media literacy and education, 2020)
"In this current period of uncertainty and introspection in the media, New Journalisms focuses not just on new challenges facing journalism, but also seeks to capture a wide range of new practices that are being employed across a diversity of media. This edited collection explores how these new practices can lead to a re-imagining of journalism in terms of practice, theory and pedagogy, bringing together high-profile academics, emerging researchers and well-known journalism practitioners. The book's opening chapters assess the challenges of loss of trust and connectivity, shifting professional identity and the demise of local journalism. A section on new practices evaluates algorithms, online participatory news websites and verification. Finally, the collection explores whether new pedagogies offer potential routes to new journalisms. Representing a timely intervention in the debate and providing sustainable impact through its forward-looking focus, New Journalisms is essential reading for students of journalism and media studies"--